Analisis Sikap dan Kepuasan Petani terhadap Benih Padi Hibrida Pendekatan Multiatribut Fishbein dan Customer Satisfaction Index (Studi Kasus Desa Wonokarto Kecamatan Sekampung Kabupaten Lampung Timur) - Feby Musti Ariska (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Understanding farmers' attitudes and satisfaction towards hybrid seeds is essential in agriculture. This research aims to determine farmers' attitudes and satisfaction with using hybrid seeds using the Fishbein Multiattribute approach and the Customer Satisfaction Index. This research was carried out in April 2022. The farmers studied already had good experience running hybrid rice farming in Wonokarto Village, Sekampung District. The number of farmer respondents interviewed was 23, who were selected using purposive sampling techniques, namely farmers who used hybrid rice seeds. The approaches used in this research are the Fishbein Multiattribute approach and the Customer Satisfaction Index (CSI) approach. The results of the study show that based on the results of data processing using the Fishbein Multiattribute approach, there are five attributes of hybrid rice seeds that are considered the most important by farmers (marketing of produce, seed price, selling price of grain, seed productivity and seed availability). The calculation results show that the analysis of farmers' attitudes towards hybrid rice seeds obtained a total score of 609.14, which means that the hybrid rice seeds can meet the farmers' expectations and needs. Meanwhile, based on the analysis of farmer satisfaction levels regarding using hybrid rice seeds using the Customer Satisfaction Index (CSI) approach, a farmer satisfaction index of 72.96% (0.7296) was obtained. This value is in the range of 0.66 – 0.80, which means farmers are satisfied with hybrid rice seeds. By paying attention to farmers' attitudes and satisfaction with mixed seeds, stakeholders can design more effective policies, programs, and strategies to support sustainable agriculture and improve farmer welfare.